2021
DOI: 10.1155/2021/6625952
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Triggered Autophagy Is Involved in PFOS-Induced Apoptosis of Human Embryo Liver L-02 Cells

Abstract: The liver is the primary target organ for perfluorooctane sulphonate (PFOS), a recently discovered persistent organic pollutant. However, the mechanisms mediating hepatotoxicity remain unclear. Herein, we explored the relationship between reactive oxygen species (ROS) and autophagy and apoptosis induced by PFOS in L-02 cells, which are incubated with different concentrations of PFOS (0, 50, 100, 150, 200, or 250 μmol/L) for 24 or 48 hrs at 37°C. The results indicated that PFOS exposure decreased cell activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Selected in vitro studies (published since 2010) exploring toxic effects of PFAS are summarised in Table 4. Majority of the presented in vitro studies investigated the impact of PFOA and/or PFOS, while the main observed effects were on thyroid [213][214][215][216] and hepatic cells [217][218][219][220][221]. In vitro exposure of thyroid cells to different PFAS was shown to have varied thyroid-disrupting effects.…”
Section: In Vitro Studies On Pfas Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Selected in vitro studies (published since 2010) exploring toxic effects of PFAS are summarised in Table 4. Majority of the presented in vitro studies investigated the impact of PFOA and/or PFOS, while the main observed effects were on thyroid [213][214][215][216] and hepatic cells [217][218][219][220][221]. In vitro exposure of thyroid cells to different PFAS was shown to have varied thyroid-disrupting effects.…”
Section: In Vitro Studies On Pfas Effectsmentioning
confidence: 99%
“…As a result, the authors came to the conclusion that short-chain PFCs had no acute cytotoxic effect on thyroid cells in vitro [216]. Some of the in vitro studies explored liver toxicity of the PFAS by investigating the occurrence of the oxidative stress on different hepatic cell lines [218,219], as well as apoptosis/autophagy [219] and cholesterol/bile acids level [221]. The impact of PFOS, PFOA, PFHxS, PFNA, PFDA, PFUnA, and PFDoA on the same cell line (HepG2) has been tested.…”
Section: In Vitro Studies On Pfas Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even with increased affinity for these nuclear receptor pathways, another in vitro study has shown that PFAS exposures to hepatic cells reduce expression of phase I and II detoxification enzymes, including cytochrome P450s (1A2, 2C19, and 3A4), glutathione-S-transferase (M1), and UDP-glucuronosyltransferase (1A1) [ 35 ]. Pathologically, both in vivo and in vitro studies have found increased oxidative stress, autophagy, or apoptosis due to PFAS exposures [ 36 , 37 , 38 , 39 ]. Despite these many recent advances, many of the health consequences of PFAS exposures are not fully understood, and additional studies are required to comprehensively characterize PFAS toxicity.…”
Section: Introductionmentioning
confidence: 99%